Hubungan antara Asupan Zat Gizi dan Pertumbuhan Tinggi Badan pada Atlet Remaja di Indonesia: A Cross Sectional Study: Hubungan antara Asupan Zat Gizi dan Pertumbuhan Tinggi Badan pada Atlet Remaja di Indonesia: Studi Potong Lintang - Penggalih, Mirza Hapsari Sakti Titis; Isnanta, Raden; Rahadian, Bayu; Margono, Margono; Sujadi, Dadi; Wicaksari, Sifa Aulia; Reswati, Vigur Dinda Yulia; Indriyani, Sinta; Niamilah, Ibtidau (Amerta Nutrition, 2024)
Background: Adequate nutritional intake in young athletes is important to support physical activity, growth, development, recovery, and performance. Inadequate intake may result in non-optimal growth and performance. Objectives: This study aimed to assess the association between nutrient intake and height among adolescent athletes in Indonesia. Methods: This cross-sectional study was conducted during May-August 2022 in 5 athlete training centers in Indonesia. There were 330 athletes aged 12-18 years old who participated in study. The primary variables consisted of sociodemographic status, body height, nutritional status and nutrient intake. Results: Median age of subjects was 16 years old, and predominately participating in sports more as strength athletes (66.1%) compared to endurance. Median height was 165 (140.4–191.5) cm, and the proportion of stunted was 3% and overweight-obese was 15.2%. Nutrient intakes per day were energy as 2,050 (582–4,355) kcal, protein 70.9 (15.9–184.4) g, fat 74.9 (11.3–230) g, carbohydrate 263.9 (65.1–708.4) g, calcium 347.6 (21.1–4507.5) mg, and vitamin D 1.80 (0–62.80) mg. The adequacy of energy was 71.2 (18.1–209.7)%, protein 67.5 (13.2–162.1)%, fat 61.3 (6.3–255.6)%, and carbohydrate 87.9 (13.8–352.9)%. Macronutrient intakes were significantly higher in endurance than strength subjects. Significant associations were found between energy, fat and carbohydrate intake with height and z-score height for age (p<0.05); while protein intake was significantly associated with body height. Conclusions: Energy, protein, fat, and carbohydrate intake were significantly associated with adolescent athletes' height. Optimizing macronutrients among athletes, especially height-oriented sports, is necessary for supporting athletes' performance.